2007
DOI: 10.1016/j.jcrs.2007.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Contact inhibition of migrating lens epithelial cells at the capsular bend created by a sharp-edged intraocular lens after cataract surgery

Abstract: Lens epithelial cells at the capsular bend of sharp-edged IOLs were in the G(0) phase of the cell cycle, indicating that they were contact inhibited. These findings support the theory the sharp posterior optic edge of the IOL inhibits LEC migration, reducing formation of posterior capsule opacification. Whether these LECs can reactivate when the capsular bend is eliminated by later formation of a Soemmerring's ring requires further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
109
0
8

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(118 citation statements)
references
References 23 publications
1
109
0
8
Order By: Relevance
“…Ключевыми технологическими моментами в реше-нии проблемы вторичной катаракты являются внутри-капсульная фиксация ИОЛ с формированием кругового капсулярного барьера вокруг ее оптической части, адге-зия ЗКХ к линзе, что предполагает использование ИОЛ с соответствующими свойствами [1,2]. Имеет значение темп трансформации капсульного мешка хрусталика.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Ключевыми технологическими моментами в реше-нии проблемы вторичной катаракты являются внутри-капсульная фиксация ИОЛ с формированием кругового капсулярного барьера вокруг ее оптической части, адге-зия ЗКХ к линзе, что предполагает использование ИОЛ с соответствующими свойствами [1,2]. Имеет значение темп трансформации капсульного мешка хрусталика.…”
Section: Discussionunclassified
“…Современные представления о предотвращении вторичной катаракты базируются на теории 'no spaceno cells' , которая предполагает определенный стандарт взаимоотношений между капсульным мешком хруста-лика (КМХ) и интраокулярной линзой (ИОЛ), фор-мируемый в процессе послеоперационной трансфор-мации капсульного мешка и его адаптации к новому содержимому [1,2].…”
Section: актуальностьunclassified
See 1 more Smart Citation
“…Although this in vitro model cannot replicate the bending of the capsular bag that occurs in vivo, correctly sizing the device will result in a tight capsular bend in the peripheral bag at the square edge. 12 This stretching of the posterior capsule should eliminate space between the capsule and the PM and in turn present both the square edge 12 and the Sharklet-patterned PM as mechanical barriers to LEC migration. To validate these results, PMs will be tested in an established rabbit model for PCO.…”
Section: Discussionmentioning
confidence: 99%
“…9 Additionally, IOLs, designed with sharp corners at the optic edge, form a physical barrier to cell migration, and reduce but do not eliminate PCO. [10][11][12][13] Although incidence of PCO has decreased since the introduction of sharp-edge IOLs in clinical practice, clinical studies have shown that LECs migrated across the sharp edge of the IOL optic in 58% of cases, preferentially at the optic-haptic junction in both one-and three-piece IOL designs. 10,14 Recently, a disc-shaped haptic design has emerged as an innovative alternative to these traditional IOL designs.…”
Section: Introductionmentioning
confidence: 99%